Development of Fermentation-induced Soymilk Gel: Effects of Different Lactic Acid Bacteria on the Physicochemical Characteristics - Fatemeh Rahmani; Ali Moayedi; Marteza Khomeiri; Mahboobeh Kashiri (مجله پژوهش‌های علوم و صنایع غذایی ایران)
Nowadays, plant-based dairy alternatives have gained considerable attention. However, the textural and sensorial characteristics of plant-based products limit their acceptance. The exploitation of lactic acid bacteria has been proposed as a promising approach to developing plant-based dairy analogs. In this study, the performance of three proteolytic lactic acid bacteria in the induction of soymilk gelation was compared and their effects on the physicochemical properties of resulting gels were investigated. Lactiplantibacillus plantarum MCM4, Streptococcus thermophilus, and Weissella confusa MDM8) were inoculated to the soy milk matrix, and incubated at 37 °C until reaching pH 4.7. To understand the effects of acidifying and proteolytic activity of starter culture, syneresis, cell counts, free amino acid content (O-phthalaldehyde method), evaluation of proteolysis using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and textural parameters of soymilk gels during fermentation were investigated. There was a significant difference among the strains in terms of viable cell counts and proteolytic activity during fermentation (p < 0.05). The amount of syneresis was also different among the resulted gels as it was in the range from 61% (sample fermented with S. thermophilus) to 69.5% (fermented with L. plantarum MCM4). The main soy proteins were degraded to different extents as a function of fermentation time. Texture analysis showed that fermentation of soymilk with W. confusa MDM8 resulted in soy gel with higher firmness and consistency, while the sample fermented with L. plantarum MCM4 had higher adhesiveness and viscosity index. Overall, it can be concluded that L. plantarum MCM4, W. confusa MDM8, and S. thermophilus can be introduced as starter cultures for the production of novel soymilk gels with reasonable properties.